Analisis Manajemen Humas dalam Upaya Penanganan Covid-19 di SPBU 142051135 Jalan Pantai Labu Lubuk Pakam - Zein, M. Ciko; Harahap, Nursapia; Abidin, Syahrul (Communication & Social Media, 2023)
This research aims to analyze the public relations management carried out in the effort to handle Covid-19 at SPBU 142051135 Jalan Pantai Labu Lubuk Pakam. It adopts a qualitative descriptive approach and refers to Dozier & Broom's theory (1995). Data were collected through observation, interviews, and documentation, and then analyzed using data collection, data reduction, data presentation, and conclusion drawing stages. The study provides an understanding of public relations management practices that can serve as a reference for similar organizations in facing crisis situations like the Covid-19 pandemic. The findings of this research are expected to offer valuable insights for the development of effective public relations management strategies to address similar challenges in the future. The results of the research indicate that the public relations management implemented at SPBU 142051135 Jalan Pantai Labu Lubuk Pakam in handling Covid-19 has effectively implemented various policies to minimize the spread of the virus. These efforts include distributing masks to visitors and implementing strict health protocols with the support of the local police.